CLINICAL AND LABORATORY CHARACTERISTICS AND OUTCOME OF COVID-19 PATIENTS ADMITTED TO THE ISOLATION WARD OF A PUBLIC SECTOR HOSPITAL - Ismail, Shumaila; Dhiloo, Azizullah Khan; Manzoor, Sohaima; Batool, Farzana; Baqi, Shehla (Journal of Postgraduate Medical Institute, 2021)
Objective: To evaluate the clinical and laboratory presentation and outcome of COVID-19 patients admitted to a public sector hospital in Pakistan. Methodology: This is a retrospective, cross sectional chart review of COVID-19 patients admitted to Dr. Ruth K.M Pfau Civil Hospital Karachi Isolation Ward from 28th February till May 28th 2020. Results: Out of 306 admitted patients, 216 (70%) tested SARS CoV-2 positive of whom median age was 45. COVID-19 was asymptomatic in 35 (16.2%), non-severe in 112 (51.9%), severe in 55 (25.5%) and critical in 14 (6.5%) patients. Severe/critical as compared to asymptomatic/non-severe disease was associated with co-morbidities (37 [53.6%] vs 35 [23.8%], p value <0.001), shortness of breath (50 [72.5%] vs 34 [23.1%], p value <0.001). Median [IQR] values demonstrated lower oxygen saturation (90 [87-92] vs 97 [97-98], p value <0.001) and lower absolute lymphocyte counts (1.3×109/L [0.9-1.82] vs 1.7×109/L [1.1-2.2], p value <0.001) with higher neutrophil to lymphocytic ratio (5.2 [3.3-8.4] vs 2.5 [1.6-3.7], p value <0.001), lactate dehydrogenase level (360U/L [271-566] vs 296U/L [207-377], p value <0.001), C-reactive protein (89mg/L [36-179] vs 19mg/L [0.9-91], p value <0.001) and ferritin level (580mg/L [331-1021] vs 341mg/L [163-679], p value <0.001). Of 216 patients, 2 (0.9%) died in the ward, whereas 13 (6%) were shifted to ICU of whom 12 died. Overall mortality was 14 (6.5%). Conclusion: In COVID-19 patients admitted to a public sector hospital, severe disease was associated with co-morbidities and elevated inflammatory markers. Mortality was very high in those that required ICU care.